2021
DOI: 10.18071/isz.74.0409
|View full text |Cite
|
Sign up to set email alerts
|

Parry-Romberg syndrome: is it a “relapsing-remitting” disease?

Abstract: Parry-Romberg syndrome, also known as progressive hemifacial atrophy, is a rare, slowly progressive disorder characterized by unilateral, painless atrophy of the skin and subcutaneous tissue of the face. Neurological manifestations such as epilepsy, migraine and trigeminal neuralgia are relatively common and accompany in 15-20% of cases. Various etiologies such as infection, trauma, embryonic developmental dysfunction, sympathetic dysfunction and autoimmune disorders have been suggested as possible causes. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The presence of autoimmune antibodies, including antinuclear antibodies, anticentromere antibodies, antihistone antibodies, and rheumatoid factors, in some patients with PRS indicated that autoimmunity may have a pathogenic role in PRS. 3,11,12 In addition, sympathetic dysfunction may also be associated with the occurrence of PRS. This hypothesis was supported by the presence of PRS-related clinical manifestations in animals with removal of the superior cervical ganglion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of autoimmune antibodies, including antinuclear antibodies, anticentromere antibodies, antihistone antibodies, and rheumatoid factors, in some patients with PRS indicated that autoimmunity may have a pathogenic role in PRS. 3,11,12 In addition, sympathetic dysfunction may also be associated with the occurrence of PRS. This hypothesis was supported by the presence of PRS-related clinical manifestations in animals with removal of the superior cervical ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that PRS may be an autoimmune disease on the same disease spectrum as localized scleroderma. The presence of autoimmune antibodies, including antinuclear antibodies, anticentromere antibodies, antihistone antibodies, and rheumatoid factors, in some patients with PRS indicated that autoimmunity may have a pathogenic role in PRS 3,11,12 . In addition, sympathetic dysfunction may also be associated with the occurrence of PRS.…”
Section: Discussionmentioning
confidence: 99%